Fiber Type-Specific Satellite Cell Content in Cyclists Following Heavy Training with Carbohydrate and Carbohydrate-Protein Supplementation - McKenzie, Alec I.; D'Lugos, Andrew C.; Saunders, Michael J.; Gworek, Keith D.; Luden, Nicholas D. (Frontiers in Physiology, 2016)
The central purpose of this study was to evaluate the fiber type-specific satellite cell and myonuclear responses of endurance-trained cyclists to a block of intensified training, when supplementing with carbohydrate (CHO) vs. carbohydrate-protein (PRO). In a crossover design, endurance-trained cyclists (n=8) performed two consecutive training periods, once supplementing with CHO (de facto ‘control’ condition) and the other with PRO. Each training period consisted of 10 days of intensified cycle training (ICT – 120% increase in average training duration) followed by 10 days of recovery (RVT – reduced volume training; 33% volume reduction vs. normal training). Skeletal muscle biopsies were obtained from the vastus lateralis before and after ICT and again following RVT. Immunofluorescent microscopy was used to quantify SCs (Pax7+), myonuclei (DAPI+), and myosin heavy chain I (MyHC I). Data are expressed as percent change ± 90% confidence limits. The 10-day block of ICTCHO increased MyHC I SC content (35 ± 28%) and myonuclear density (16 ± 6%), which remained elevated following RVTCHO (SC = 69 ± 50% vs. PRE; Nuclei = 17 ± 15% vs. PRE). MyHC II SC and myonuclei were not different following ICTCHO, but were higher following RVTCHO (SC = +33 ± 31% vs. PRE; Nuclei = 15 ± 14% vs. PRE), indicating a delayed response compared to MyHC I fibers. The MyHC I SC pool increased following ICTPRO (37 ± 37%), but without a concomitant increase in myonuclei. There were no changes in MyHC II SC or myonuclei following ICTPRO. Collectively, these trained endurance cyclists possessed a relatively large pool of SCs that facilitated rapid (MyHC I) and delayed (MyHC II) satellite cell proliferation and myonuclear accretion with CHO. The current findings strengthen the growing body of evidence demonstrating alterations in SC number without hypertrophy. SC pool expansion is typically viewed as an advantageous response to exercise. However, when coupled with our previous report that PRO possibly enhanced whole muscle recovery and increased MyHC I and II fiber size, the limited satellite cell/myonuclear response observed with carbohydrate-protein seem to indicate that protein supplementation was beneficial and may have minimized the necessity for satellite cell involvement.